Evaluation Report on Western Ghats Development Programme in Maharashtra (A Joint Study) - Planning Commission (Planning Commission, 1996)
At the instance of the Planning Commission, the Programme Evaluation Organisation (PEO) and the Directorate of Economics and Statistics (DES), Maharashtra undertook a joint evaluation study of the Western Ghats Development Programme (WGDP) in the State of Maharashtra. The study is concerned primarily with the evaluation of performance, implementation and impact of WGDP in the State. Accordingly, the study was designed to reflect on the physical and financial performance vis-a-vis targets in various sectoral activities, whether the implementation of the programme is in accordance with the guidelines and on the impact of the programme on the intended beneficiaries and agriculture and ecology of the region. In addition to the data base available with the Planning Department, Government of Maharashtra, the study required project and beneficiary level information on a number of parameters in order to meet the aforesaid objectives. This information was collected through structured questionnaires canvassed to the taluka and watershed-level officers and to beneficiary and non beneficiary households. For detailed scrutiny at the micro level, a sample of 4 districts- two each from 'ghat' and 'coastal' regions, 8 talukas, 36 watersheds, 59 works, 266 beneficiary and 65 non-beneficiary households were selected, using a multistage stratified sample design. The design and instruments developed for the study were approved by a Group of Advisers.
A Joint Study
Government of India Programme Evaluation Organisation Planning Commission